The Effect of Price, Location, and Promotion on Customer Retention Behavior NR Beauty Salon &; Make Up Pengging Boyolali - Susy Herawati; Lyna Lyna (ProBisnis : Jurnal Manajemen, 2023)
This study aims to analyze the effect of Price, Location, and Promotion on Customer Retention. The population in this study were 40 consumers of NR Beauty Salon & Make Up Pengging Boyolali. Sampling in this study used a non probability sampling method, namely a sampling technique that does not provide equal opportunities or opportunities for its members. The sample in this study were 40 consumers. Data collection using a questionnaire. Data analysis was performed by using multiple linear regression analysis with the SPSS 25.00 application. The results showed that the significance value of the t test of the Price variable had a significant effect on Customer Retention with a significance value of 0.000, and price was the most dominant variable on customer retention with a value of 4.105, Location had a significant effect on Customer Retention with a significance value of 0.002, Promotion had a significant effect on Customer Retention with a significance value of 0.001, and a significance value for the F test variables Price, Location, Promotion have an effect on Customer Retention simultaneously by 0.000. From these results it can be concluded that all independent variables affect Customer Retention partially and simultaneously.